Dezvoltarea serviciilor în bibliotecile publice: Loredana Stanciu - admin, admin (BIBLIOPOLIS, 2022)
In the 21st century, when information is flowing with astonishing speed and text production is uncontrollable, librarians are not only showing their passion for books, multiple skills or abilities, but also their ability to collaborate. Public libraries do not need better people to be the hubs of communities, but to work with the right partners. The article describes the need to implement a management that includes development strategies targeted at specific objectives. Their future will depend on how they know how to build their strategies. Libraries will no longer be represented only by books and buildings, but also in terms of the type and quality of services offered. The article highlights the benefits of interacting with people around libraries and that good service planning will guide the development direction towards the best results.